Design of the on board computer (OBC) for the X-SAT, LEO microsatellite - Tan, Kim Leng. (2008)
A case study of a specific design of the OBC - the microsatellite that is being built in Nanyang Technological University (NTU), called the X-Sat. The X-Sat has three payloads, of which one of these payloads is an imaging payload which requires handling of high bit rate data (at close to 100Mbps) and agile attitude maneuvers. A specific OBC architecture is developed for these needs.